2020
DOI: 10.1016/j.bja.2020.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Minimising haemodynamic lability during changeover of syringes infusing norepinephrine in adult critical care patients: a multicentre randomised controlled trial

Abstract: Background: Arterial pressure lability is common during the process of replacing syringes used for norepinephrine infusions in critically ill patients. It is unclear if there is an optimal approach to minimise arterial pressure instability during this procedures. We investigated whether 'double pumping' changeover (DPC) or automated changeover (AC) reduced blood pressure lability in critically ill adults compared with quick syringe changeover (QC). Methods: Patients requiring a norepinephrine infusion syringe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Recent clinical research has demonstrated that, independent of the changeover strategy used, at least 25% of critical haemodynamic events occurred around changeover when administering norepinephrine to critically ill adult patients. 21 Beside start-up delays, dead volume effects and pressure differences between the i.v. catheter and the newly connected syringe pump also seem to be responsible for the observed under or over infusion.…”
Section: Clinical Tip 10: Minimise Pump Start-up Delays and Flow Irre...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent clinical research has demonstrated that, independent of the changeover strategy used, at least 25% of critical haemodynamic events occurred around changeover when administering norepinephrine to critically ill adult patients. 21 Beside start-up delays, dead volume effects and pressure differences between the i.v. catheter and the newly connected syringe pump also seem to be responsible for the observed under or over infusion.…”
Section: Clinical Tip 10: Minimise Pump Start-up Delays and Flow Irre...mentioning
confidence: 99%
“…Microinfusions are run continuously and fresh infusions are required on a regular basis. Recent clinical research has demonstrated that, independent of the changeover strategy used, at least 25% of critical haemodynamic events occurred around changeover when administering norepinephrine to critically ill adult patients 21 . Beside start-up delays, dead volume effects and pressure differences between the i.v.…”
Section: Clinical Tip 10: Minimise Pump Start-up Delays and Flow Irre...mentioning
confidence: 99%
“…Syringe is a medical device used to inject liquids into patients. [1][2][3][4][5] The syringe has 3 major components: the plunger, the barrel, and the needle. [6][7][8][9][10] The commonly used materials for the plunger and barrel are polypropylene [11][12][13] and materials for the needle are stainless, titanium, or other coated materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, this so called microinfusion strategy uses syringe infusion pumps that are associated with considerable start‐up delays of fluid delivery resulting in prolonged lag times of drug effect. This is of particular importance when initiating cardiovascular drugs in hemodynamically unstable patients or during syringe changeover 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…This is of particular importance when initiating cardiovascular drugs in hemodynamically unstable patients or during syringe changeover. 2,3 In the last two decades researchers have studied different factors which affect the extent of start-up delays in syringe infusion pumps. These factors include flow rate, syringe size and architecture, syringe pump design, infusion line setup, administration of a…”
mentioning
confidence: 99%